2016 Annual report : Saint Lucia: IICA’S contribution to the development of agriculture and rural communities (2017)
The Inter-American Institute for Cooperation on Agriculture (IICA) carried out several technical activities in 2016, focusing on areas such as climate change adaptation, agro-tourism, value chain development, sustainable livelihood and enterprise development, and capacity building for primary actors in agricultural health and food safety. These objectives align with IICA's flagship project areas, including competitiveness and sustainability of agricultural chains, inclusion in agricultural and rural territories, resilience and comprehensive risk management, and productivity and sustainability of family agriculture. IICA's focus on resilience of agricultural production systems in Saint Lucia resulted in the establishment of a Climate Smart Agriculture Forum for stakeholder dialogue and coordination on climate change-related issues affecting agriculture. The forum has been a valuable learning and information-sharing mechanism. IICA also worked on the production of communication guidelines supporting improved generation of value-adding information and knowledge products that can help make agriculture systems more resilient to climate change. Additionally, IICA provided interventions for stakeholder groups on areas such as organizational development and networking, resource mobilization, entrepreneurial skill development, and capacity building on value-adding processes. The implementation of the 10th European Development Fund (EDF) Caribbean Actions under the 'Agriculture Policy Programme (APP) with focus on the Caribbean and the Pacific' and the Sanitary and Phytosanitary Measures (SPS) also benefited local stakeholders in areas of access to finance and markets, Hazard Analysis Critical Control Points (HACCP), and Traceability. Overall, IICA's technical cooperation services aim to improve agriculture's capacity to mitigate and adapt to climate change, improve productivity and competitiveness of the agriculture sector, and strengthen agriculture's contribution to food security and the well-being of the rural population.